Preparation and Properties of Segmented Quasi-Dynamic Display Device - Dengwu Wang; Fang Wang (International Journal of Antennas and Propagation)
A kind of material, microencapsulated electronic ink, was prepared and supported on ITO glass used as backplane electrode and etched panels of the words “N-P-U” as pixel electrode. In addition, a quasi-dynamic display device was designed for electronic paper. The control signal generated by monostable process of 555 counter was used to drive the relay to work. The actual output of this kind of display was also observed. Through the combination of 555 counter and relay, quasi-dynamic electronic ink display was able to be achieved at the voltage of 15 V. Furthermore, the delay time can be controlled within 0–10 seconds by adjusting monostable trigger time of the counter.